SENSIBILIDADE DE Trichoderma harzianum AOS INSETICIDAS METOMIL E TIAMETOXAM - PUCHETA, Renan Mancoelho; BLANCO, Neder Henrique Martinez; SILVA, Talísia de Souza; COSTA, Brenda Fernandes; GRAICHEN, Felipe André Sganzerla (ANAIS DO ENIC, 2025)
-